MODERN TYPES OF IMMUNOENZYME ANALYSIS METHODS OLD PROBLEMS - Kudratova Zebo Erkinovna; Tamila Abdufattoevna Umarova; Sirojeddiova Sanobar (Web of Journals Publishing, 2024)
The basis of any ELISA variant is the determination of enzymatic reaction products in the examination of tested samples in comparison with negative and positive controls. The method has high sensitivity and specificity, which is 90%.
Keywords: immunoenzymatic method, antibodies, antigen, concentration, affinity, immunocomplexes.